2016
DOI: 10.1038/srep32037
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle ATP synthesis and cellular H+ handling measured by localized 31P-MRS during exercise and recovery

Abstract: 31P magnetic resonance spectroscopy (MRS) is widely used for non-invasive investigation of muscle metabolism dynamics. This study aims to extend knowledge on parameters derived from these measurements in detail and comprehensiveness: proton (H+) efflux, buffer capacity and the contributions of glycolytic (L) and oxidative (Q) rates to ATP synthesis were calculated from the evolutions of phosphocreatine (PCr) and pH. Data are reported for two muscles in the human calf, for each subject and over a wide range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 41 publications
6
36
0
Order By: Relevance
“…Each volunteer lay supine on the ergometer, inside the MR system, with the RF coil strapped below their right calf. The knee of the volunteers was fully extended during the dynamic examination (2 min rest, 6 min exercise and 6 min recovery) to ensure a major involvement of the gastrocnemius muscles and only a minor contribution of the SOL muscle to the exercise performed 20, 21, 22. The volunteers performed plantar flexions at a workload set to about 25–35% of the maximal voluntary contraction force, once every T R (2 s).…”
Section: Methodsmentioning
confidence: 99%
“…Each volunteer lay supine on the ergometer, inside the MR system, with the RF coil strapped below their right calf. The knee of the volunteers was fully extended during the dynamic examination (2 min rest, 6 min exercise and 6 min recovery) to ensure a major involvement of the gastrocnemius muscles and only a minor contribution of the SOL muscle to the exercise performed 20, 21, 22. The volunteers performed plantar flexions at a workload set to about 25–35% of the maximal voluntary contraction force, once every T R (2 s).…”
Section: Methodsmentioning
confidence: 99%
“…The recovery of PCr is considered a valid index of mitochondrial oxidative phosphorylation [8, 1012], and has been used to study mitochondrial impairment in diseases with high socio-economic impact such as mitochondrial myopathy [13], diabetes [14], peripheral arterial disease [15, 16], and heart failure [17]. Mitochondrial ATP synthetic function in human skeletal muscle is best estimated through dynamic 31 P-MRS recording of post-exercise PCr recovery [3, 5]. These data are more easily interpreted following low intensity exercise (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…below the lactate threshold), when contribution of glycolytic ATP synthesis is considered negligible. In low intensity exercise regimes, PCr recovery follows monoexponential kinetics [5, 18], which implies a linear steady-state relationship of oxidative ATP synthesis to PCr depletion, and vice versa [1921]. 31 P-MRS data interpretation during voluntary exercise (as opposed to during recovery of PCr following exercise) is significantly more involved, and requires several assumptions about motor unit recruitment with the particular exercise protocol and workload used [22].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these improvements, Fiedler and co-workers applied localized 31 P-MRS with sufficient temporal resolution (ca. 30 s) to investigate differences in m. gastrocnemius and m. soleus during and after mechanical exercise [40,41]. This clearly revealed that the originally assumed splitting of the Pi peak into intra-and extracellular components was just an artifact due to leg motion and partial volume effect (m. gastrocnemius and m. soleus).…”
Section: P Mrs In Vivo During Exercise In Skeletal Musclementioning
confidence: 96%